HUBUNGAN KUALITAS TIDUR DENGAN INDEKS PRESTASI MAHASISWA BARU DI UNIVERSITAS SARI MULIA - Fachriyal Hami; Rian Tasalim (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2021)
Background: The quality of sleep has a major effect on psychological and physical conditions because it is a necessity that helps the formation of body cells, a healing mechanism and maintains the body’s biochemical balance. Objective: This study aims to determine, identify and analyze the effect of sleep quality on the student achievement index. Methods: This study used a quantitative approach with a cross-sectional design plus open-ended questions to explore data in depth.  Result: The statistical result shows that sleep quality does not affect the achievement index, and factors that can influence are self-management, self-efficacy, and environmental factors. Conclusion: There are 67,5% of respondents experiencing poor sleep quality, and there is so many sleep quality which is opposite with each of their achievement index, also self-management, self-efficacy, and environmental factors that influence the achievement index of students.